Overexpression of a proton-coupled vacuolar glucose exporter impairs freezing tolerance and seed germination - Klemens, Patrick A. W.; Poschet, Gernot; Büttner, Michael (The new phytologist, 2014)
Arabidopsis vacuoles harbor, besides sugar transporter of the TMT-type, an early response to dehydration like 6 (ERDL6) protein involved in glucose export into the cytosol. However, the mode of transport of ERDL6 and the plant's feedback to overexpression of its activity on essential properties such as, for example, seed germination or freezing tolerance, remain unexplored. Using patch-clamp studies on vacuoles expressing AtERDL6 we demonstrated directly that this carrier operates as a proton-driven glucose exporter. Overexpression of BvIMP, the closest sugar beet (Beta vulgaris) homolog to AtERDL6, in Arabidopsis leads surprisingly to impaired seed germination under both conditions, sugar application and low environmental temperatures, but not under standard conditions. Upon cold treatment, BvIMP overexpressor plants accumulated lower quantities of monosaccharides than the wild-type, a response in line with the reduced frost tolerance of the transgenic Arabidopsis plants, and the fact that cold temperatures inhibits BvIMP transcription in sugar beet leaves. With these findings we show that the tight control of vacuolar sugar import and export is a key requisite for cold tolerance and seed germination of plants.
First published 16 December 2016
Gesehen am 01.08.2017